Strategy for Successful Use of the Directorate General of Taxes Portal Application on Performance of Account Representative at the Tax Service Office in South Jakarta Area I - Khaerani, Fitri; Noerman, Teuku (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the success strategy of using the Directorate General of Taxes (DGT) portal application on the performance of Account Representatives (AR) at the South Jakarta I Regional Tax Office (KPP) using the Delone and McLean Model approach (1992 & 2003). In the era of digitalization of tax administration, the use of DGT applications is a major factor in increasing the effectiveness of AR services and productivity. The estimation method used is Structural Equation Modeling (SEM) to test the relationship between the variables of System Quality (X1) and Information Quality (X2) as independent variables, User Satisfaction (Y1) as a moderating variable, and User Performance (Y2) as a dependent variable. The sampling method used is a saturated sample, with a total of 221 respondents, consisting of Account Representatives at the South Jakarta I Regional Tax Office. Data collection was carried out through a questionnaire-based survey, which was then analyzed using SEM to identify the direct and indirect effects of system quality and information quality on AR performance, with user satisfaction as a moderating factor. The results of the study indicate that system quality and information quality contribute significantly to improved AR performance, both directly and through increased user satisfaction. The Delone and McLean model confirms that a more efficient digital tax system and accurate information play a crucial role in improving Account Representative task effectiveness and taxpayer satisfaction. These findings provide strategic implications for the Directorate General of Taxes in designing policies for digitizing tax services and enhancing human resource capacity in the tax administration sector.